Hematological Toxicity During Concomitant Treatment With Ruxolitinib and Avelumab for Merkel Cell Carcinoma - Buonerba, Luciana; Di Trolio, Rossella; Grimaldi, Antonio; Tucci, Aniello; Leo, Emilio; Ingenito, Concetta; Costabile, Ferdinando; Ragone, Gianluca; Savastano, Beatrice; Uzzauto, Maria Teresa; Belsito Petrizzi, Valeria; Di Lorenzo, Giuseppe (Frontiers in Oncology, 2020)
Background Merkel Cell Carcinoma (MCC) is a rare neuroendocrine skin cancer. It frequently emerges in presence of immunosuppression state as myeloprofiliferative syndromes (MS). MS are treated with Ruxolitinib, a selective JAK1 and JAK2 inhibitor. Avelumab, an Anti PDL-1 inhibitor is MCC standard treatment. At to date is unknown if avelumab and ruxolitinib have a sinergistic or antagonistic effect when used together. Methods We have identified all patients diagnosed with MCC, treated with avelumab, concomitant ruxolitinib, belonging to Tortora Hospital, Pagani and “Santa Maria La Pietà” Hospital, Nola, Italy between 1 June 2019 and 1 April 2020. Results Among 6 MCC we have found 2 patients in treatment with concomitant drugs. Both patients were in treatment with Ruxolitinib for MS at standard regimen without hematological side effects. Starting Avelumab dose we found thrombocytopenia, leukopenia and anemia after cycle 1 and cycle 4 respectively, deciding to suspend both treatments. Following the suspension the hematological values improved allowing the recovery of avelumab without resuming ruxolitinib. Conclusions The combined treatment of ruxolitinib and avelumab demonstrated severe toxicity. Modify the schedule or reduce the dose of both drugs needs to be studied in order to be able to treat both pathologies.